Neutralizing TIMP1 Restores Fecundity in a Rat Model of Endometriosis and Treating Control Rats with TIMP1 Causes Anomalies in Ovarian Function and Embryo Development - Stilley, Julie A.W. (Society for the Study of Reproduction, Inc., 2010)
Human and rat endometriotic lesions synthesize and secrete tissue inhibitor of metalloproteinase 1 (TIMP1). More TIMP1 localizes in the ovarian theca in an established rat model for endometriosis (Endo) when compared to surgical controls (Sham). We hypothesized that endometriotic TIMP1 secreted into peritoneal fluid (PF) negatively affects ovarian function and embryogenesis by altering the balance of matrix metalloproteinases (MMPs) and TIMPs. Three experiments were performed modulating TIMP1 in vitro and in vivo to investigate ovarian and embryonic anomalies. The first experiment demonstrated control embryos treated in vitro with endometriotic PF concentrations of TIMP1 developed abnormally. In the second experiment where TIMP1 was modulated in vivo, TIMP1-treated Sham rats had fewer zygotes, ovarian follicles, and corpora lutea (CLs) and poorer embryo quality and development, which is analogous to the findings in Endo rats. Importantly, Endo rats treated with a TIMP1 function-blocking antibody had zygote, follicle, and CL numbers and embryo quality similar to Sham rats. In addition, more TIMP1 inhibitory activity was found in ovaries from Endo and TIMP1-treated Sham rats than in ovaries from Sham or TIMP1 antibody-treated Endo rats. In experiment three, control rats (no surgery) treated with Endo PF had fewer follicles and CLs and increased TIMP1 localization in the ovarian theca whereas treatment with Endo PF stripped of TIMP1 or with Sham PF had no effect, providing further evidence that endometriotic TIMP1 sequesters in the ovary and inhibits MMPs necessary for ovulation. Collectively, these results showed that excessive TIMP1 was deleterious to ovulation and embryo development. Thus, novel TIMP1-modulating therapies may be developed to alleviate infertility in women with endometriosis.